Rancang Bangun Sistem Informasi Sekolah Berbasis Web Untuk Komunikasi Antara Guru Dan Orang Tua Murid Di SDN Harapan Jaya II Bekasi Menggunakan Metode String Matching - Chuzaimi, Ahmad; Basry, Asril (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
In the current era of rapid scientific and technological progress, information plays an important role in driving progress in various fields. Information technology and computers play an important role in facilitating human work and in solving various problems. This research aims to design and build a web-based school information system that facilitates communication between teachers and parents at SDN Harapan Jaya II Bekasi. This system was developed using the String Matching method to increase efficiency in searching and delivering information. With this system, it is hoped that communication between teachers and parents will be more effective and structured, and can support the overall teaching and learning process. The research results show that the system developed is able to meet the communication and information needs of the school well.